Perbandingan Sistem Pendukung Keputusan Menggunakan Metode WP Dan TOPSIS Studi Kasus Program Keluarga Harapan (PKH) Desa Kampung Kramat - Arya Dimas Setiadi; Agung Triayudi; Agus Iskandar (JURIKOM (Jurnal Riset Komputer), 2022)
PKH or the Family HopehProgram that is a conditional social assistance program for poor families as the initial basis for achieving family happiness which is a long-term problem. Therefore, the government introduced the Family Hope program (PKH) to reduce poverty. The Family Hope Program (PKH) is a social policy that provides social services in the form of cash and basic necessities to poor families who depend on school children and pregnant women for their lives. Family hope in the future, family poverty alleviation is a form of social investment in poverty alleviation. In this case, the Family Hope Program (PKH) was established in Kramat village as a forum to increase socialization and poverty alleviation. A decision support system (DSS) will be built using the weighted product (WP) method and a priority control technique similar to the ideal solution (TOPSIS) to calculate the problem